Identification of pathogenic fungi in garlic bulbs during storage and in the root zone during plant growth - M. A. Filyushin; O. A. Danilova; T. M. Seredin (Овощи России)
Relevance and methods. Losses of agricultural crops are associated not only with the development of diseases during the growing season, but also during post-harvest storage. Garlic is a popular vegetable and aromatic crop in world. Significant losses in garlic yield during cultivation and storage are associated with fungal pathogens, the most harmful of which are representatives of the genus Fusarium. In the Moscow region, the defeat of garlic by Fusarium occurs annually, but with varying intensity. At the Federal Scientific Vegetable Center (FSVC), it was shown that rot and wilting of garlic plants is caused by a complex of pathogenic fungi, including mainly different species of Fusarium. At the same time, the ratio of Fusarium species in the pathogenic complex changes from year to year, new Fusarium species and their races are registered. The aim of this study was to identify fungal phytopathogens causing dry rot of garlic cloves during post-harvest storage. To carry out the work, garlic bulbs of cultivars Dubkovsky and Strelets were taken from the FSVC storage.Results. As a result of visual examination, cloves with symptoms of dry rot were identified. The diseased cloves tissues were plated on potato dextrose agar to obtain fungal colonies. Analysis of the morphological and cultural characteristics of fungal isolates, as well as the nucleotide sequences of four DNA regions (ITS spacers, genes EF1α, RPB1, and RPB2) showed that the causative agent of dry rot of garlic cloves is the pathogenic fungus Fusarium proliferatum. In addition, in the field, identification was carried out based on the analysis of the sequences of spacers ITS and the EF1αgene of phytopathogenic fungi inhabiting the root zone of garlic plants. As a result, two species of fungi of the genus Fusarium (F. proliferatum and F. oxysporum f. sp. cepae), as well as the species Rhizoctonia solani, Volutella rosea, and Ceratobasidium sp. were found in the root zone of garlic cultivars.